«Естетична» теорія соціалістичного реалізму - Ксьондзик, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
This article studies the peculiarities of the aesthetic theory of socialist realism, which in reality quite differs from our usual vision of any kind of aesthetics. The phenomenon of permanent politicization of literary-art and its modification according to faulty bases and principles is shown. All these factors are presented as the causes of slow disintegration of the method of socialist realism in literary practice and theory, despite its future influences on all modern literary process.